Production of Zn-doped TiO2 film with enhanced photocatalytic activity - DEMİRCİ, SELİM (My University, 2022)
In this study, zinc (Zn)-doped titanium dioxide (TiO2) films were prepared using the two steps: anodic oxidation method and heat treatment process. The crystal structure, morphology and elemental composition of the Zn-doped TiO2 films were investigated. These films were characterized by scanning electron microscopy (SEM) with energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The results indicated that the TiO2 films with clear, uniform and short nanopores had a high surface area and high degree of crystallinity. The results showed that the asanodized TiO2 film was successfully obtained as anatase phase at 450 degrees C. The results of XPS analysis confirmed the presence of Zn in the lattice of TiO2 as dopant, and thermal diffusion technique was successfully done as doping method. The photocatalytic performances of the Zn-doped TiO2 films were evaluated in terms of their photodegradation rate of methylene blue (MB) in an aqueous solution under UV light irradiation. The results revealed that the Zn-doped TiO2 film had a higher photocatalytic activity in comparison with the undoped sample. This study inspired that Zn-doped TiO2 films are a great potential material to treat wastewater in industrial field.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, SERAMİK; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, CERAMICS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); General Materials Science; Ceramics and Composites; Physical Sciences; Zinc; TiO2 films; XPS; Photocatalytic activity; Hydrothermal method; METHYLENE-BLUE; THIN-FILMS; NANOPARTICLES; DEGRADATION; DIFFUSION; SURFACE; TRANSPARENT; VACANCIES; OXIDE; AU; Zinc; TiO2 flms; XPS; Photocatalytic activity; Hydrothermal method